PENGARUH FINANCIAL LITERACY DAN FINANCIAL BEHAVIOR TERHADAP MINAT INVESTASI - Ni Made Mustini; Tiara Kusuma Dewi; Laras Oktaviani (JUIMA : JURNAL ILMU MANAJEMEN, 2024)
This research aims to determine the influence of Financial Literacy and Financial Behavior on investment interest. Investing is one way to manage finances. When someone is interested in investing, that person already has sufficient financial knowledge or literacy regarding current economic conditions and is supported by an attitude in managing finances well (Financial Behavior). This research is quantitative research with data collection methods using questionnaires distributed to 101 students of the accounting study program at Triatma Mulya University. This research was assisted by the SPSS 22 statistical tool. The results of this research show that Financial Literacy and Financial Behavior have a significant effect on investment interest and have a contribution of 81.6%, the remaining 18.4% is influenced by other variables not included in this research.